2003
DOI: 10.2320/matertrans.44.2339
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Nano WC particles in WC-Co Alloys during Liquid-Phase Sintering

Abstract: WC-10Co-xVC alloys were produced using two different sizes of WC powders (200 nm and 4.4 mm) via planetary milling and a liquidphase sintering technique. When VC was added to the WC-Co alloys, the growth of WC particles was effectively suppressed. However, this process was dependent on the amount of additive used. Since the average WC particle size became less than 1 mm, the system experienced a significant loss in carbon, resulting in the formation of an undesirable phase. The goal of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In particular, hardness measured by indentation methods strongly depends on the testing load and time [16]; thus, the hardness of a sample can vary. Dense WC sintered bodies are also difficult to obtain by general vacuum sintering, and several studies have reported that carbon-deficient phases, such as W 2 C, that are softer than WC are frequently detected in WC sintered bodies [13,16,17,44]. Therefore, the experimental hardnesses are lower than the calculated hardnesses.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…In particular, hardness measured by indentation methods strongly depends on the testing load and time [16]; thus, the hardness of a sample can vary. Dense WC sintered bodies are also difficult to obtain by general vacuum sintering, and several studies have reported that carbon-deficient phases, such as W 2 C, that are softer than WC are frequently detected in WC sintered bodies [13,16,17,44]. Therefore, the experimental hardnesses are lower than the calculated hardnesses.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Additionally, reduced hardness with increased binder content is less in cemented carbides with finer WC grains than with micron-sized WC [5]. Fine grain sizes have high sintering rates because of the large interfacial surface area between the WC particles and the binder [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several explanations for the role of the grain growth inhibitors have been proposed, e.g. the preferential segregation of V or Cr [16,17], the lower surface energy of WC due to the presence of V or Cr [18], and the inhibiting effect of those carbides on the dissolution of WC in a Co melt [19]. Even though grain growth inhibitors are able to maintain the small size of WC, the addition of VC and Cr 2 C 3 promotes the formation of a phase (W 3 Co 3 C), (W,V)C [20] and an M 7 C 3 -type carbide [21], both of which degrade the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%